Examining Tobacco Use among Secondary School Teachers: A Case Study of Nepalgunj Sub-Metropolitan City - Acharya, Lal Mani (Academia Research Journal, 2024)
Tobacco consumption is the most significant preventable risk factor for morbidity and mortality worldwide, affecting both developing and developed countries. Among school teachers, the use of tobacco products represents not only a detrimental habit but also a poor financial decision, a severe health risk, and a negative example for students. This cross-sectional, analytical study examines the prevalence and associated factors of tobacco use among 148 secondary school teachers in Nepalgunj Sub-Metropolitan City. Data were collected through structured questionnaires, and prevalence rates were calculated using SPSS. Chi-square tests were employed to analyze the associated factors. The overall prevalence of tobacco use in any form among the teachers was 17.6%, with nearly all users being male. Female teachers were found to be 13.12 times less likely to use tobacco compared to their male counterparts. Specifically, 15 respondents reported smoking tobacco products, 17 reported using smokeless tobacco products, and 6 used both forms. More than 62% of respondents began using tobacco between the ages of 16 and 25. The reasons for initiating tobacco use included pleasure (42.3%), stress reduction (30.79%), curiosity (15.38%), and peer pressure (11.53%). The high prevalence of tobacco use among secondary school teachers in Nepalgunj is concerning, especially given their educational background. Only 1% of female teachers reported using any form of tobacco, likely due to prevailing social norms. Despite their education, many teachers indicated the need for specific training to effectively teach students about the dangers of tobacco use. This underscores the necessity for targeted training programs to equip teachers with the skills and techniques needed to discourage tobacco use among students.